Strategi Pemasaran Produk Pada PT. Keraton Agri Nusantara - Zahwa Nuril Firdausiah (Universitas Islam Kadiri, 2023)
This study aims to analyze the marketing strategy at PT. Keraton Agri Nusantara especially the marketing strategy implemented by the company. Then to find out the results of the analysis of Strengths, Weaknesses, Opportunities, and Threats as well as an overview of the strategies so that they can be applied to increase product sales. By using the SWOT research technique, Matrix, EFAS, and IFAS as well as quadrant diagrams. This research uses a qualitative method, namely a case study that produces descriptive data set forth in words. Data collection techniques in this study the authors made a direct visit to PT. Keraton Agri Nuantara to conduct interviews with business owners. The conclusion from the analysis carried out on the marketing strategy of PT. Keraton Agri Nusantara is a SWOT analysis calculation as outlined in the PT quadrant diagram. Keraton Agri Nusantara is in quadrant 1 position, namely Growt. PT. Keraton Agri Nusantara has many opportunities and strengths so that it can seize and take advantage of existing opportunities while minimizing weaknesses and overcoming various threats.